Introduction to a special section on the supervisee's perspective of reflective supervision/consultation. Issue 2 (1st April 2022) - Barron, Carla C.; Eaves, Tanika
Abstract: The definition and implementation of reflective supervision/consultation (RS/C) in the infant early childhood mental health field (IECMH) has largely been driven by expert supervisors, researchers, and leaders in the field. The voice of the frontline practitioner, the most likely recipient of RS/C has had less prominence in the scholarly discourse, leaving unclear supervisees' perspectives on the meaning and value of RS/C. This special section addresses supervisees' experiences with RS/C across five studies. In the first two papers, researchers examined supervisees' perspectives on essential components of RS/C and perceived impacts of RS/C on their work. In paper 3, researchers report on perceived associations between RS/C and professionals' well‐being. The fourth paper addresses experiences in RS/C and professionals' use of reflective practices. Finally, researchers in the fifth paper present the psychometric properties of an observational tool that focuses on the interaction between supervisors and supervisees. Collectively, the studies promote understanding about supervisees' perspectives and experiences that may benefit future research studies aimed at investigating the role of RS/C in well‐being and practice and provide information for program administrators considering the inclusion of RS/C in professional development efforts. Resumen: La definición e implementación de la supervisión/consulta con reflexión (RS/C) en el campo de la salud mental infantil y la temprana niñez (IECMH) ha sido, por la mayor parte, llevada a cabo por supervisores expertos, investigadores y líderes en ese campo. La voz de quienes practican en el frente de trabajo, quienes tienen la mayor probabilidad de recibir RS/C, ha tenido menos prominencia en los acercamientos científico‐profesionales, dejando no claras las perspectivas de los supervisados acerca del significado y valor de RS/C. Esta sección especial se refiere a las experiencias de los supervisados con RS/C a través de cinco estudios. En los dos primeros ensayos, los investigadores examinaron las perspectivas de los supervisados acerca de componentes esenciales de RS/C y cómo perciben el impacto de RS/C en su trabajo. En el tercer ensayo, los investigadores reportan sobre la percepción de asociaciones entre RS/C y el bienestar de los profesionales. El cuarto artículo enfoca las experiencias en cuanto a RS/C y el uso que los profesionales hacen de las prácticas de reflexión. Finalmente, los investigadores en el quinto ensayo presentan las propiedades sicométricas de una herramienta de observación que se enfoca en la interacción entre supervisores y supervisados. Colectivamente, los estudios promueven la comprensión acerca de las perspectivas y experiencias de los supervisados que pudieran beneficiar los futuros estudios investigativos cuya meta sea investigar el papel de RS/C en el bienestar y la práctica, así como aportar información para administradores de programas que estén considerando la inclusión de RS/C en los esfuerzos de desarrollo profesional. Résumé: La définition et la mise en place de la supervision/consultation réflective (abrégé selon l'anglais RS/C) dans le domaine de la santé mentale du nourrisson et de la petite enfance (IECMH) ont largement été élaborées par les experts superviseurs, les chercheurs et les leaders dans le domaine. La voix du praticien de première ligne, le plus à même d'être le récipiendaire de la RS/C, a eu moins de prominence dans le discours scientifique, menant ainsi à un manque de clarté concernant les perspectives des personnes supervisées sur la signification et la valeur de la RS/C. Ce numéro spécial aborde les expériences des personnes supervisées au moyen de la RS/C au travers de cinq études. Dans les deux premiers articles les chercheurs ont examiné les perspectives des personnes supervisées sur les composants essentiels de la RS/C et leurs impacts perçus de la RS/C sur leur travail. Dans le troisième article les chercheurs se sont penchés sur les liens perçus entre la RS/C et le bien‐être des professionnels. Le quatrième article porte sur des expériences dans la RS/C et l'utilisation des pratiques réflectives faites par des professionnels. Enfin les chercheurs du cinquième article présentent les propriétés psychométriques d'un outil observationnel qui se concentre sur l'interaction entre les superviseurs et les supervisées ou supervisés. Collectivement ces études mettent en valeur la compréhension entre les perspectives et les expériences des personnes supervisées qui peuvent profiter aux recherches à venir s'attachant à explorer le rôle de la RS/C dans le bien‐être et la pratique. Elles présentent aussi des renseignements utiles pour les administrateurs de programme qui considèrent l'inclusion de la RS/C dans leurs efforts de la formation professionnelle. Zusammenfassung: Einleitung zum Sonderteil über die Perspektive von Supervisand:innen auf reflexive Supervision/Beratung Die Definition und Umsetzung von reflexiver Supervision/Beratung (reflective supervision/consultation; RS/B) im Bereich der frühkindlichen psychischen Gesundheit (infant early childhood mental health; IECMH) wurde größtenteils von Supervisionsexpert:innen, Forschenden und Führungskräften in diesem Bereich vorangetrieben. Die Stimme von Fachkräften aus der Praxis, die am ehesten von RS/C profitieren, hat im wissenschaftlichen Diskurs weniger Gewicht, sodass die Perspektiven der Supervisand:innen bezüglich der Bedeutung und des Werts von RS/C unklar bleiben. Dieser Sonderteil widmet sich fünf Studien, in denen die Erfahrungen von Supervisand:innen mit RS/C untersucht werden. In den ersten beiden Beiträgen untersuchten Forschende die Sichtweisen von Supervisand:innen auf die wesentlichen Komponenten von RS/C und die wahrgenommenen Auswirkungen von RS/C auf ihre Arbeit. In Beitrag 3 geht es um wahrgenommene Zusammenhänge zwischen RS/C und dem Wohlbefinden der Fachkräfte. Der vierte Beitrag befasst sich damit, wie RS/C erlebt wird und der Anwendung reflexiver Praktiken durch die Fachkräfte. Im fünften Beitrag schließlich stellen Forschende die psychometrischen Eigenschaften eines Beobachtungsinstruments vor, das die Interaktion zwischen Supervisor:innen und Supervisand:innen misst. Zusammengenommen fördern die Studien das Verständnis für die Perspektiven und Erfahrungen von Supervisand:innen, was zukünftigen Studien zugutekommen kann, die die Rolle von RS/C für das Wohlbefinden und in der Praxis untersuchen. Außerdem können sie Führungskräfte oder Entscheidungstragende informieren, die die Einbeziehung von RS/C in die berufliche Entwicklung ihres Personals in Betracht ziehen. 抄録: タイトル スーパーバイジーの視点からの内省的スーパービジョン/コンサルテーションに関する特集の紹介 乳幼児期の精神保健分野 (IECMH) における内省的スーパービジョン/コンサルテーション (RS/C) の定義と実施は、だいたいにおいて、熟練のスーパーバイザー、研究者、現場のリーダーによって推進されてきた。しかし、RS/Cの受け手である可能性が最も高い最前線の実践者の声は、学術的な議論ではあまり注目されず、RS/Cの意味や価値に関するスーパーバイジーの視点は不明確なままである。本特集では、5つの研究におけるRS/Cに関するスーパーバイジーの経験を取り上げる。最初の2つの論文では、RS/Cの本質的な構成要素に関するスーパーバイジーの視点と、RS/Cが彼らの仕事に与える影響の認識について調査している。論文3では、研究者らはRS/Cと専門家の幸福との関連の認識について報告している。論文4では、RS/Cの経験と専門家の内省的実践の活用について述べている。最後に、5番目の論文で、研究者らはスーパーバイザーとスーパーバイジーの間の相互作用に焦点を当てた観察方法の心理測定学的特性を示している。総合的に、これらの研究は、スーパーバイジーの視点と経験についての理解を促進し、幸福と実践におけるRS/Cの役割を調査することを目的とした将来の調査研究に役立ち、専門家開発の取り組みにRS/Cを含めることを検討しているプログラム管理者に情報を提供するものである。 摘要: 婴儿早期心理健康 (IECMH) 领域反思性监督/咨询 (RS/C) 的定义和实施在很大程度上是由该领域的专家主管、研究人员和领导者推动的。一线从业者 (最有可能的RS/C接受者) 的声音在学术话语中的地位较低, 这就导致受监督者对RS/C的意义和价值的看法不明确。本节介绍了受监督者在五项研究中接受RS/C的经验。在前两篇论文中, 研究人员考察了受监督者对RS/C基本组成部分的看法, 以及RS/C对他们工作的感知影响。在第三篇论文中, 研究人员报告了RS/C与专业人员幸福感之间的感知关联。第四篇论文讨论了RS/C的经验和专业人员对反思性实践的使用情况。最后, 研究人员在第五篇论文中介绍了一种观察工具的心理测量学特性, 该工具侧重于监督者和受监督者之间的互动。总的来说, 这些研究促进了对受监督者的观点和经验的理解, 这可能有益于未来旨在调查RS/C在幸福感和实践中的作用的研究, 并为考虑将RS/C纳入专业发展工作的项目管理人员提供信息。 ملخص: مقدمة لقسم خاص حول منظور الخاضع للإشراف عن الإشراف / الاستشارة التأملية إن تعريف وتنفيذ الإشراف / الاستشارة التأملية (RS / C) في مجال الصحة النفسية للطفولة المبكرة للرضع (IECMH) كان مدفوعًا إلى حد كبير بمشرفين خبراء وباحثين وقادة في هذا المجال. ولكن كان لصوت ممارس الخط الأمامي ، وهو المتلقي للإشراف التأملي ، أهمية أقل في الخطاب الأكاديمي ، تاركًا وجهات نظر الخاضعين للإشراف غير واضحة حول معنى وقيمة الإشراف والاستشارة التأملية. يتناول هذا القسم الخاص تجارب الخاضعين للإشراف من خلال خمس دراسات. في الورقتين الأوليين ، قام الباحثون بتقديم وجهات نظر الخاضعين للإشراف حول المكونات الأساسية للإشراف والاستشارة التأملية والتأثيرات المتصورة لها على عملهم. في الورقة الثالثة ، قدم الباحثون تقريرًا عن الارتباطات المتصورة بين الإشراف والاستشارة التأملية ورفاهية المهنيين. تتناول الورقة الرابعة الخبرات في مجال الإشراف التأملي واستخدام المتخصصين للممارسات التأملية. أخيرًا ، قدم الباحثون في الورقة الخامسة الخصائص السيكومترية لأداة الملاحظة التي تركز على التفاعل بين المشرفين والخاضعين للإشراف . بشكل إجمالي ، تعزز الدراسات فهم وجهات نظر وخبرات الخاضعين للإشراف التي قد تفيد الدراسات البحثية المستقبلية الهادفة إلى التحقيق في دور الإشراف التأملي في الرفاهية والممارسة وتوفير معلومات لمديري البرامج مع مراعاة إدراج هذه الممارسات في جهود التطوير المهني .